1975
DOI: 10.1093/ajcn/28.12.1458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of betel nut and fermented fish on the thiamin status of northeastern Thais

Abstract: Thiamin deficiency could result either from inadequate intake of thiamin or consumption of food containing antithiamin factors. Dietary surveys conducted in northeastern Thailand indicated that both thiamin and caloric intake of subjects under studies were sufficient. In Thailand, correlation exists between the consumption of food containing antithiamin factors and the prevalence of thiamin deficiency. Betel nuts and raw fermented fish possess antithiamin activity. Abstention from both betel nut chewing and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…The negative relation found between fish and thiamin, although fish contains fair amounts of thiamin, may be an artefact explained by the small between individuals variability of fish intake in the country-90% of the population eat fish every day-and residual confounding as fish correlated positively with alcohol (which relates negatively to thiamin) and negatively with meat and vegetables (which both relate positively to thiamin). An eVect caused by anti-thiamin activity in fish is unlikely as such an antithiamin activity has been reported in raw or fermented fish [39][40][41] both of which are almost never consumed in Seychelles. Tea has also been reported to be associated with low blood thiamin caused by thiaminase, inhibition of thiamin utilisation, reduced urinary excretion of thiamin, and reduced erythrocyte transketolase activity.…”
Section: Discussionmentioning
confidence: 99%
“…The negative relation found between fish and thiamin, although fish contains fair amounts of thiamin, may be an artefact explained by the small between individuals variability of fish intake in the country-90% of the population eat fish every day-and residual confounding as fish correlated positively with alcohol (which relates negatively to thiamin) and negatively with meat and vegetables (which both relate positively to thiamin). An eVect caused by anti-thiamin activity in fish is unlikely as such an antithiamin activity has been reported in raw or fermented fish [39][40][41] both of which are almost never consumed in Seychelles. Tea has also been reported to be associated with low blood thiamin caused by thiaminase, inhibition of thiamin utilisation, reduced urinary excretion of thiamin, and reduced erythrocyte transketolase activity.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Betel nut has also been shown to possess antithiamine activity. [19] Both fish and betel nut are consumed widely in this region. The reporting of such cases necessitates the need for a larger study to explore the role of such dietary ingredients in precipitating such devastating manifestations in apparently healthy individuals.…”
mentioning
confidence: 99%
“…ROS can cause many harmful effects such as oxidative and chromosomal damage of DNA, which could be involved in several stages of the carcinogenic process in oral mucosa. 36,37 Some studies found that use of betel nut was associated with thiamine deficiency, 38,39 aggravated effects of vitamin-D deficiency 40 and was associated with central obesity, hyperglycemia, diabetes mellitus 41,42 cirrhosis 43 and goiter. 44 Various studies have shown that betel nut use during pregnancy has adverse effect on birth outcomes, including low birth weight, shorter birth length, and preterm delivery.…”
Section: Health Hazardmentioning
confidence: 99%